2009
DOI: 10.1103/physrevb.79.035324
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction investigation of a three-dimensional Si/SiGe quantum dot crystal

Abstract: High-resolution x-ray diffraction was employed to study the structural properties of a three-dimensional periodic arrangement of SiGe quantum dots in a Si matrix. Using extreme ultraviolet lithography at a synchrotron source a two-dimensional array of pits ͑period 90ϫ 100 nm 2 ͒ was defined and transferred into a ͑001͒ Si wafer by reactive ion etching. By molecular-beam epitaxy SiGe islands of about 30 nm diameter and 3 nm height were grown into the pits. Subsequent deposition of Si spacer layers of 10 nm thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 55 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…Therefore, we evaluate the integrated intensity as a function of satellite order and fit it with the corresponding data of our simulations. 38 The result is shown for the centre of the design 1 wafer in Fig. 4.…”
Section: Physical Characterizationmentioning
confidence: 99%
“…Therefore, we evaluate the integrated intensity as a function of satellite order and fit it with the corresponding data of our simulations. 38 The result is shown for the centre of the design 1 wafer in Fig. 4.…”
Section: Physical Characterizationmentioning
confidence: 99%
“…Without the patterned substrate, the dots exhibited random lateral distribution and lower size uniformity, and the wetting layers became thicker compared with those on the patterned regions. 6,12 The results obtained from these random QDs are also shown in Fig. 3 and exhibit a much weaker resonance feature even with thicker wetting layers.…”
Section: Three-dimensional Phononic Nanocrystal Composed Of Ordered Qmentioning
confidence: 67%
“…Sample details can be found elsewhere. 2,6 Arrangement of these QDs composed a nanoscaled cubic crystal with lattice constants of 11 ͑denoted by L͒, 90, and 100 nm. The first step to investigate the consequent phononic band gaps is based on a 3D FDTD method.…”
Section: Three-dimensional Phononic Nanocrystal Composed Of Ordered Qmentioning
confidence: 99%
See 1 more Smart Citation
“…The wave functions of carriers confined in periodically arranged quantum wells may overlap creating minibands of eigenenergies with broad optoelectronical applications. 5 The formation of regularly ordered QDs arrays is usually obtained during the growth of crystalline multilayers ͑MLs͒, 6,7 where the mismatch of the lattice parameters causes elastic forces which induce QDs ordering. Some very recent studies 3,4 showed the possibility of the production of spatially correlated Ge QDs also in amorphous MLs, where the ordering is achieved by the interplay of diffusion and surface morphology mechanisms.…”
Section: Formation Of Long-range Ordered Quantum Dots Arrays In Amorpmentioning
confidence: 99%